ANALYSIS OF THE APPLICATION OF LABELLING THEORY IN INDONESIAN IMMIGRATION GLASSES: A CASE STUDY OF NIGERIAN DIPLOMATS WHO ARE SUSPECTED TO BE VICTIMS OF "MURSERY" BY THE IMMIGRATION OFFICERS IN SOUTH JAKARTA - Hana Farah Dhiba; Fachrizza Sidi Pratama; Rafsanjani Ismarus (Journal of Law and Border Protection, 2022)
The misunderstanding of the video footage of Immigration officers checking Nigerian foreigners which went viral on social media which then created various speculations and misunderstandings in the community. However, the circulating footage only shows when the officers fought and defended themselves against the foreigner and the foreigner shouted "I can't breathe, I can't breathe" thus making the atmosphere cloudy. The case of alleged mistreatment of Nigerian diplomats by unscrupulous immigration officers has attracted public attention and has become a trending topic in various media. This indirectly causes various versions of the series of events that appear on social media. Our society and Indonesian immigration officers are applying the theory of labeling sequentially, the process starts with the primary deviance, namely by naming Nigerian citizens as rioters or perpetrators of violations and secondary deviance applies because since the label was given to Nigerian citizens, the level of crimes committed has increased and always there every year. the second reaction is that the community is against it, this happens because they have a negative stigma and give a bad label to black citizens including Nigerian citizens. Therefore, they confirmed that in handling and securing the Nigerian citizens, immigration officers had to use violence for fear of unwanted things such as the WN running away, rebelling and the like.